Do Exit Options Increase the Value-For-Money of Public-Private Partnerships? - Marco Buso; Cesare Dosi; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2020)
We study the effects of granting an exit option that enables the private party to early terminate a PPP project if it turns out to be financially loss-making. In a continuous-time setting with hidden information about operating profits, we show that an exit option, acting as a risk-sharing device, can soften agency problems and, in so doing, accelerate investment and increase the government's expected payoff, even while taking into account the costs that the public sector will have to meet in the future to take direct responsibility on service provision.
Keywords: D81; D82; D86; H54; 330; Public Infrastructure Services; Public-Private Partnerships; Adverse Selection; Real Options; Early Termination Fees